Attachment Patterns and their Relationship with Relationship Crisis Management during the Engagement Period in Jordan - Al-Arman, Khawla Mahmoud; Al-Mahaireh , Abdallah Salem (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to explore the relationship between attachment patterns and the management of relationship crisis between partners during the engagement period in Jordan. Methods: The study employed a descriptive correlational approach. Two scales were used: the Attachment Patterns Scale and the Relationship Crisis Management Scale. The study sample consisted of a convenient sample of 412 engaged individuals in Jordan. Results: The results revealed that the most prevalent attachment pattern among engaged individuals during the engagement period was the secure attachment pattern, with a percentage of 92.7%. The avoidant attachment pattern followed at a percentage of 3.9%, while the least common pattern was the anxious attachment pattern at 3.4%. Furthermore, the results also showed a high level of relationship crisis management among engaged individuals during the engagement period. A positive linear relationship was found between secure attachment style and relationship crisis management, while an inverse relationship was observed between anxious and avoidant attachment patterns and relationship crisis management between partners. Conclusions: The results underscore the importance of considering attachment patterns and relationship crisis management during the engagement period in Jordan and reflect the need for developing educational and therapeutic plans to comprehend attachment patterns and their role in influencing crisis management processes, to arrive at effective solutions for facing and managing crises.